Laminated coil component
By setting an appropriate gap between the mounting surface of the laminated coil component and the coil, the crack problem caused by stress during installation is solved, and the stability and durability of the component are achieved.
Patent Information
- Application Number
- CN202411304240.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2024-09-19
- Publication Date
- 2025-03-28
AI Technical Summary
When mounting the laminated coil components, stress may cause cracks in the body.
The first gap in the first direction is provided between the coil and the mounting surface on the cross section viewed from the third direction, so that the ratio of the size of the element in the first direction is 12 to 30%, so as to ensure the distance between the mounting surface and the coil and suppress the occurrence of cracks.
It effectively suppresses cracks caused by stress during installation, ensuring the stability and durability of the laminated coil components.
Smart Images

Figure CN119724825A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated coil component. Background Art
[0002] A laminated coil component including an element body and a coil disposed inside the element body is known (for example, Japanese Patent Application Publication No. 2012-060049). In Patent Document 1, the coil has a coil axis extending in a predetermined direction. When viewed from the direction in which the coil axis extends, the coil has a rectangular shape. Summary of the invention
[0003] The laminated coil component having the above-mentioned structure is mounted on the mounting substrate by configuring the coil axis to extend along the mounting substrate. The laminated coil component is mounted with one side surface of the element body as the mounting surface opposite to the substrate. Here, when the laminated coil component is mounted on the mounting substrate, stress is applied to the mounting surface side, which may cause cracks in the element body.
[0004] An object of one embodiment of the present invention is to provide a laminated coil component capable of suppressing cracks caused by stress during mounting.
[0005] The present invention provides a stacked coil component, comprising: a body having a pair of first side surfaces opposite to each other in a first direction, and a pair of second side surfaces opposite to each other in a second direction orthogonal to the first direction; and a coil, which is arranged inside the body and the coil axis extends along a third direction orthogonal to the first direction and the second direction, one of the pair of first side surfaces is a mounting surface, and in a cross section observed from the third direction, a first gap in the first direction between the coil and the mounting surface is 12 to 30% of the size of the body in the first direction.
[0006] The laminated coil component includes a coil, which is arranged inside the element body, and the coil axis extends along a third direction orthogonal to the first direction and the second direction. In addition, one of a pair of first side surfaces opposite to each other in the first direction is a mounting surface. Therefore, the laminated coil component is mounted in a configuration in which the coil axis extends along the surface of the mounting substrate. At this time, stress is applied to the mounting surface of the laminated coil component due to the expansion, contraction, etc. of the conductor layer of the mounting substrate. In contrast, in a cross section observed from the third direction, the ratio of the first gap in the first direction between the coil and the mounting surface to the size of the element body in the first direction is 12 to 30%. In this case, a distance for suppressing cracks can be ensured between the mounting surface and the coil, which are easily deformed by stress in the element body. Thus, cracks caused by stress during installation can be suppressed.
[0007] The first gap may be larger than the second gap in the second direction between the coil and the second side surface in the cross section viewed from the third direction. In this case, a distance sufficient to suppress cracks can be ensured between the mounting surface of the element body that is easily deformed by stress and the coil.
[0008] The first gap may be 1.2 to 6.0 times the second gap. In this case, a distance sufficient to suppress cracking can be ensured between the mounting surface of the element body that is easily deformed by stress and the coil.
[0009] It can be that the first region between the mounting surface and the coil in the element body forms a surface region constituting the mounting surface and an internal region closer to the inner side than the surface region, and the surface region has a larger average crystal grain size than the internal region. In this case, the generation of cracks on the mounting surface can be suppressed in the surface region with a large average crystal grain size. On the other hand, even when cracks are generated on the mounting surface, the internal region with a small average crystal grain size and pores can also suppress the advancement of cracks to the inside.
[0010] The surface region may be 2 to 25% of the first region. In this case, the effect of suppressing the occurrence of cracks on the mounting surface in the surface region and the effect of suppressing the propagation of cracks in the internal region can be obtained in a balanced manner.
[0011] The stacked coil component of the present invention may be, which comprises: a body having a pair of first side surfaces opposite to each other in a first direction, and a pair of second side surfaces opposite to each other in a second direction orthogonal to the first direction; and a coil, which is arranged inside the body, and the coil axis extends along a third direction orthogonal to the first direction and the second direction, one of the pair of first side surfaces is a mounting surface, and in a cross section observed from the third direction, a first gap in the first direction between the coil and the mounting surface is larger than a second gap in the second direction between the coil and the second side surface.
[0012] The laminated coil component includes a coil, which is arranged inside the element body, and the coil axis extends along a third direction orthogonal to the first direction and the second direction. In addition, one of a pair of first side surfaces opposite to each other in the first direction is a mounting surface. Therefore, the laminated coil component is mounted in a configuration in which the coil axis extends along the surface of the mounting substrate. At this time, stress is applied to the mounting surface of the laminated coil component due to the expansion, contraction, etc. of the conductor layer of the mounting substrate. In contrast, in a cross section observed from the third direction, the first gap in the first direction between the coil and the mounting surface can be larger than the second gap in the second direction between the coil and the second side surface. In this case, a distance for suppressing cracks can be ensured between the mounting surface and the coil, which are easily deformed by stress in the element body. Thus, cracks caused by stress during installation can be suppressed.
[0013] The first gap may be 1.2 to 6.0 times the second gap. In this case, a distance sufficient to suppress cracking can be ensured between the mounting surface of the element body that is easily deformed by stress and the coil.
[0014] According to the present invention, cracks caused by stress during mounting can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a perspective view showing a laminated coil component according to one embodiment.
[0016] Figure 2 Yes means Figure 1 An exploded perspective view of the layer structure of the laminated coil component is shown.
[0017] Figure 3 This is a cross-sectional view of a mounting structure when a laminated coil component is mounted on a mounting substrate.
[0018] Figure 4 middle, Figure 4 (a) is along Figure 3 The cross-sectional view of line IVa-IVa shown in FIG. Figure 4 (b) is a cross-sectional view of a laminated coil component of a comparative example.
[0019] Figure 5 This is an enlarged cross-sectional view of the vicinity of the mounting surface as viewed from the Y-axis direction.
[0020] Figure 6 This is a diagram for explaining the principle that cracks may occur when mounting a laminated coil component.
[0021] Figure 7 This is a photo of the first area.
[0022] Figure 8 It is a graph showing the experimental results.
[0023] Fig. 9 It is a cross-sectional view showing a laminated coil component according to a modified example.
[0024] Description of Reference Numerals
[0025] 1... stacked coil component; 2... element body; 2c, 2d... side surface (first side surface); 2e, 2f... side surface (second side surface); 10... coil; E1... first area; EA... surface area; EB... internal area; G1... first gap; G2... second gap; MF... mounting surface; L... center axis. DETAILED DESCRIPTION
[0026] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. In the description of the drawings, the same or corresponding elements are denoted by the same reference numerals, and repeated descriptions are omitted.
[0027] Figure 1 It is a perspective view showing a laminated coil component according to one embodiment. Figure 2 Yes means Figure 1 An exploded perspective view of the layer structure of the laminated coil component is shown. Figure 3 This is a cross-sectional view of a mounting structure when a laminated coil component is mounted on a mounting substrate.
[0028] like Figure 1 As shown, the laminated coil component 1 includes a body 2 in a substantially rectangular parallelepiped shape and a pair of external electrodes 4, 5 respectively arranged at both ends of the body 2. The body 2 has a pair of end faces 2a, 2b opposite to each other, and four side faces 2c, 2d, 2e, 2f extending along the relative directions of the pair of end faces 2a, 2b in a manner of connecting the pair of end faces 2a, 2b as outer surfaces. Here, the direction opposite to the end faces 2a, 2b is set as the Y-axis direction (third direction). The direction opposite to the side faces 2c, 2d is set as the Z-axis direction (first direction). The direction opposite to the side faces 2e, 2f is set as the X-axis direction (second direction). The X-axis direction is a direction orthogonal to the Z-axis direction. The Y-axis direction is a direction opposite to the X-axis direction and the Z-axis direction. The end face 2a is arranged on the positive side of the Y-axis direction, and the end face 2b is arranged on the negative side. The side face 2c is arranged on the positive side of the Z-axis direction, and the side face 2d is arranged on the negative side. 2e is arranged on the positive side of the X-axis direction, and 2f is arranged on the negative side.
[0029] like Figure 2 As shown, the element body 2 is formed by stacking a plurality of insulating layers 11. Each insulating layer 11 is rectangular (in this embodiment, a rectangular shape) and has four sides 11c, 11d, 11e, and 11f that divide the side surfaces 2c, 2d, 2e, and 2f. Each insulating layer 11 is an insulator having electrical insulation properties and is composed of a sintered body of an insulating green sheet. In the actual element body 2, each insulating layer 11 is integrated to the extent that the boundaries between them cannot be identified.
[0030] The insulating layer 11 may be made of ferrite (for example, Ni—Cu—Zn ferrite, Ni—Cu—Zn—Mg ferrite, Cu—Zn ferrite, or Ni—Cu ferrite).
[0031] The size of the element body 2 in the Z-axis direction is defined as size L1. Size L1 is the distance between the side surfaces 2c and 2d in the Z-axis direction. The size of the element body 2 in the X-axis direction is defined as size L2. Size L2 is the distance between the side surfaces 2e and 2f in the X-axis direction. The size of the element body 2 in the Y-axis direction is defined as size L3 (refer to Figure 3). Dimension L3 is the distance between the end faces 2a and 2b in the Y-axis direction. Dimension L1 can be greater than 200μm, and can be greater than 250μm. In addition, dimension L1 can be less than 450μm, and can be less than 300μm. Dimension L2 can be greater than 120μm, and can be greater than 170μm. In addition, dimension L2 can be less than 320μm, and can be less than 210μm. Dimension L3 can be greater than 250μm, and can be greater than 340μm. In addition, dimension L3 can be less than 600μm, and can be less than 380μm. However, each dimension is not limited to these ranges.
[0032] The external electrode 4 is formed to cover the entire end face 2a and a part of the four side faces 2c, 2d, 2e, and 2f. The external electrode 5 is formed to cover the entire end face 2b and a part of the four side faces 2c, 2d, 2e, and 2f. The stacking direction of the plurality of insulator layers 11 coincides with the relative direction of the pair of end faces 2a and 2b. Therefore, the pair of external electrodes 4 and 5 are respectively arranged at the two ends of the element body 2 in the stacking direction of the plurality of insulator layers 11. The external electrode 4 is arranged on the positive side in the Y-axis direction. The external electrode 5 is arranged on the negative side in the Y-axis direction.
[0033] Each external electrode 4, 5 is formed by attaching a conductive paste mainly composed of copper, silver, gold, nickel, or chromium to the outer surface of the element body 2, sintering it, and then performing electroplating. Cu, Ni, Sn, etc. can be used for electroplating. The conductive paste is applied by, for example, a dip coating method, a printing method, or a transfer method. The plating process is, for example, electrolytic plating or electroless plating. Through the plating process, a plating layer is formed on the outer surface of the conductive paste.
[0034] like Figure 2 As shown, the laminated coil component 1 includes a plurality of coil patterns 12 and a connecting portion 13. The connecting portion 13 includes a lead conductor 14 and a connecting conductor 15. The plurality of coil patterns 12, the lead conductors 14, and the connecting conductors 15 are arranged side by side along the stacking direction of the insulating layer 11 in the element body 2. Each coil pattern 12, the lead conductor 14, and the connecting conductor 15 include, for example, a conductive material such as copper, silver, gold, nickel, palladium, or chromium. Each coil pattern 12, the lead conductor 14, and the connecting conductor 15 is constituted as a sintered body of a conductive paste containing the above-mentioned conductive material. The conductor pattern that becomes each conductor 12, 14, 15 is formed by screen printing the conductive paste using a screen plate having openings corresponding to the conductor pattern.
[0035] The conductor patterns 21 forming the coil pattern 12 are each formed in a substantially U-shape. A substantially circular land portion 23 corresponding to the through-hole conductor 22 is formed at one end and the other end of the conductor pattern 21. The conductor patterns 21 are connected in series via the through-hole conductor 22 in a state where the phases are shifted by 90 degrees, forming a coil axis L (see Figure 3 ) The coil 10 extends along the stacking direction. The coil axis L of the coil 10 extends along the Y-axis direction. In addition, the number of turns of the coil 10 is not particularly limited.
[0036] The conductor pattern 24 forming the lead conductor 14 is composed of a substantially circular pad portion (pad conductor) 26 corresponding to the through-hole conductor 25. That is, the lead conductor 14 is composed of the through-hole conductor 25 and the pad portion 26 provided integrally with the through-hole conductor 25. The outer end portions of the lead conductor 14 are exposed at the end faces 2a and 2b in the stacking direction of the element body 2 and are connected to the external electrodes 4 and 5. The lead conductor 14 is arranged at the center of the insulating layer 11.
[0037] The conductor pattern 27 forming the connection conductor 15 is formed in a straight line so as to connect the position corresponding to one pad portion 23 of the coil pattern 12 and the position corresponding to the pad portion 26 of the lead conductor 14. At one end of the conductor pattern 27, a substantially circular pad portion 28 corresponding to the through-hole conductor 25 is coaxial with the pad portion 26 of the lead conductor 14 and is formed in substantially the same shape, and at the other end of the conductor pattern 27, a substantially circular pad portion 29 corresponding to the through-hole conductor 22 is coaxial with the pad portion 23 of the coil pattern 12 and is formed in substantially the same shape. Figure 2 As shown, one end of the conductor pattern 27 is connected to the other end of the lead conductor 14 via the via-hole conductor 25 , and the other end of the conductor pattern 27 is connected to the end of the coil pattern 12 via the via-hole conductor 22 .
[0038] like Figure 3 As shown, the laminated coil component 1 is mounted on the mounting substrate 100. The mounting substrate 100 includes a substrate 101, conductor layers 102, 103, and resists 104, 105. The substrate 101 is a flat plate material that becomes a base member of the mounting substrate 100. The conductor layers 102, 103 are formed on the surface of the substrate 101 by a conductive material. The conductor layers 102 and 103 are arranged to be separated from each other in the Y-axis direction. The resists 104, 105 are insulating layers that cover the surfaces of the conductor layers 102, 103. The resists 104, 105 expose the conductor layers 102, 103. The laminated coil component 1 is mounted on the mounting substrate 100 with one side 2d of a pair of side surfaces 2c, 2d as a mounting surface MF. The external electrode 4 is electrically connected to the conductor layer 102, and the external electrode 5 is electrically connected to the conductor layer 102. The external electrode 4 and the conductor layer 102 are fixed by solder 106. The external electrode 5 and the conductor layer 103 are fixed by solder 107. The laminated coil component 1 is mounted on the mounting substrate 100 in a state where the coil axis L extends along the surface of the substrate 101.
[0039] Next, refer to Figure 4 (a) of the present invention will describe in detail the structure of the conductor pattern 21 forming the coil pattern 12. Figure 4 As shown in (a), the cross section of the element body 2 and the coil 10 has a rectangular shape with the Z-axis direction as the long side direction and the X-axis direction as the short side direction. The coil 10 has a pair of coil conductors 31 and 32 extending along the X-axis direction as the short side direction, and a pair of coil conductors 33 and 34 extending along the Z-axis direction as the long side direction. In addition, the cross-sectional shape of the element body 2 and the coil 10 is not particularly limited, and can be a rectangular shape with the X-axis direction as the long side direction and the Z-axis direction as the short side direction, or a square shape.
[0040] The coil conductors 31 and 32 are separated from each other in the Z-axis direction, the coil conductor 31 is arranged on the positive side of the Z-axis direction, and the coil conductor 32 is arranged on the negative side of the Z-axis direction. The coil conductor 31 is arranged at a position separated from the side surface 2c to the negative side in the Z-axis direction. The coil conductor 32 is arranged at a position separated from the side surface 2d to the positive side in the Z-axis direction. The coil conductors 33 and 34 are separated from each other in the X-axis direction, the coil conductor 33 is arranged on the positive side of the X-axis direction, and the coil conductor 34 is arranged on the negative side of the X-axis direction. The coil conductor 33 is arranged at a position separated from the side surface 2e to the negative side in the X-axis direction. The coil conductor 34 is arranged at a position separated from the side surface 2f to the positive side in the X-axis direction.
[0041] The positive end and negative end of the coil conductor 33 in the Z-axis direction are connected to the positive end of the coil conductor 31 and 32 in the X-axis direction. The positive end and negative end of the coil conductor 34 in the Z-axis direction are connected to the negative end of the coil conductor 31 and 32 in the X-axis direction. Thus, the coil conductors 31, 32, 33, and 34 form a rectangular ring shape when viewed from the Y-axis direction. In addition, Figure 4 The coil pattern 12 shown in (a) has coil conductors 32, 33, and 34, which are opened on the positive side in the Z-axis direction. Figure 4 The same relationship also holds true for the coil pattern 12 other than that shown in (a).
[0042] Next, the dimensional relationship of the laminated coil component 1 is described. The size of the gap in the Z-axis direction between the coil 10 and the mounting surface MF on the cross section observed from the Y-axis direction is set as the first gap G1. The size of the gap in the X-axis direction between the coil 10 and the side surfaces 2e and 2f on the cross section observed from the Y-axis direction is set as the second gap G2. The size of the first gap G1 is the size in the Z-axis direction between the edge on the negative side of the Z-axis direction of the coil conductor 32 and the side surface 2d. The size of the second gap G2 is the size in the X-axis direction between the edge on the positive side of the X-axis direction of the coil conductor 33 and the side surface 2e. Alternatively, the size of the second gap G2 is the size in the X-axis direction between the edge on the negative side of the X-axis direction of the coil conductor 34 and the side surface 2f. In addition, the second gap G2 on the coil conductor 33 side and the second gap G2 on the coil conductor 34 side may be different and may be different from each other. In this case, the average value of the second gap on the coil conductor 33 side and the second gap on the coil conductor 34 side is used as the second gap G2. In addition, when the dimension in the Z-axis direction between the edge of the positive side in the Z-axis direction of the coil conductor 31 and the side surface 2c is set as the third gap G3, the third gap G3 may have the same dimension as the first gap G1. However, the third gap G3 may also have a dimension different from that of the first gap G1. The third gap G3 may have the same dimension conditions as the first gap G1 below. However, the dimension relationship of the third gap G3 is not particularly limited, and it may not have the dimension conditions of the first gap G1.
[0043] In the cross section observed from the Y-axis direction, the first gap G1 in the Z-axis direction between the coil 10 and the mounting surface MF is larger than the second gap G2 in the X-axis direction between the coil 10 and the side surfaces 2e and 2f. Specifically, the first gap G1 can be more than 1.2 times or more than 1.8 times the second gap G2. Thus, a distance for suppressing cracks can be ensured between the mounting surface MF and the coil 10 that are deformed due to stress in the element 2. The first gap G1 can be less than 6.0 times or less than 3.0 times the second gap G2. Thus, the reduction in inductance characteristics caused by the reduction in the inner diameter of the coil can be suppressed. When the upper limit is exceeded, the inner diameter of the coil sometimes decreases, resulting in a reduction in inductance characteristics.
[0044] In the cross section observed from the Y-axis direction, the ratio of the first gap G1 to the size of the element 2 in the Z-axis direction, that is, the dimension L1, can be 12% or more, or 18% or more. Thus, a distance for suppressing cracks can be ensured between the mounting surface MF deformed by stress in the element 2 and the coil 10. In addition, in the cross section observed from the Y-axis direction, the ratio of the first gap G1 to the size of the element 2 in the Z-axis direction, that is, the dimension L1, can be 30% or less, or 25% or less. Thus, the reduction in inductance characteristics caused by the reduction in the inner diameter of the coil can be suppressed. When the upper limit is exceeded, the inner diameter of the coil is sometimes reduced, resulting in a reduction in inductance characteristics.
[0045] Figure 5 This is an enlarged cross-sectional view of the vicinity of the mounting surface MF as viewed from the Y-axis direction. Figure 5 As shown, the first area E1 between the mounting surface MF and the coil 10 in the element 2 forms a surface area EA constituting the mounting surface MF, and an internal area EB that is closer to the inside than the surface area EA. The surface area EA is an area having a predetermined thickness from the side 2d to the positive side in the Z-axis direction. The internal area EB is an area that is closer to the positive side in the Z-axis direction than the surface area EA. The surface area EA and the internal area EB can be formed in substantially the entire area in the Y-axis direction of the element 2. The surface area EA is an area with a larger average grain size than the internal area EB. Such a surface area EA is formed by making the sinterability of the surface area EA higher than that of the internal area EB. The ratio of the average grain size of the surface area EA to the average grain size of the internal area EB can be in the range of 1.2 to 2.0. In addition, the average grain size of the surface area EA is not particularly limited and can be set to 0.5 to 3.0 μm. The thickness of the surface area EA is not particularly limited and can be set to 2 to 8 μm.
[0046] The surface area EA may be more than 2% of the first area E1, or more than 3%. In this case, the surface area EA can ensure a thickness for suppressing the generation of cracks. The surface area EA may be less than 25% of the first area E1, or less than 20%. In addition, the ratio of the surface area EA to the first area E1 may be the average value of the ratio of the thickness of the surface area EA to the thickness of the first area E1 in the Z-axis direction at each position in the X-axis direction. In this case, the thickness of the internal area EB sufficient to suppress the progress of cracks can be ensured. In addition, the second area E2 between the side 2c in the element 2 and the coil 10, the third area E3 between the side 2e in the element 2 and the coil 10, and the fourth area E4 between the side 2f in the element 2 and the coil 10 may have a layer structure with the same purpose as the first area E1.
[0047] Next, the operation and effects of the laminated coil component 1 according to the present embodiment will be described.
[0048] The laminated coil component 1 includes a coil 10, which is arranged inside the element body 2, and the coil axis L extends along the Y-axis direction which is orthogonal to the Z-axis direction and the X-axis direction. In addition, the side surface 2d, which is one of the pair of side surfaces 2c and 2d facing each other in the Z-axis direction, is the mounting surface MF. Therefore, the laminated coil component 1 is mounted in a configuration in which the coil axis L extends along the surface of the mounting substrate 100 (refer to Figure 3 At this time, stress is applied to the mounting surface MF of the laminated coil component 1 due to the influence of expansion, contraction, etc. of the conductor layers 102 and 103 of the mounting substrate 100 .
[0049] Here, refer to Figure 4 (b) and Figure 6 , a comparative example of a laminated coil component 200 is described. Figure 4 As shown in (b), the first gap G1 and the second gap G2 of the laminated coil component 200 are equal. In addition, the ratio of the first gap G1 to the dimension L1 of the element body 2 is less than 12%. Figure 6 , the principle of cracks that may occur when installing laminated coil components is explained. Figure 6 As shown in (a) of FIG. 1 , paste solder 108 is applied to the conductor layers 102 and 103 of the mounting substrate 100. Then, the laminated coil component 200 is mounted on the conductor layers 102 and 103 via the paste solder 108. Figure 6 As shown in (b), when solder reflow mounting is performed, the conductor layers 102 and 103 of the mounting substrate 100 expand in the high-temperature reflow furnace. The conductor layers 102 and 103 expand toward the center of the element body 2. Figure 6 As shown in (c), when the reflow is completed and the temperature decreases, the conductor layers 102 and 103 shrink in a manner away from the central position of the element body 2. As for the shrinkage stress of the conductor layers 102 and 103, stress is applied in a manner that horizontally stretches the mounting surface MF of the stacked coil component 1 mounted via solders 106 and 107. At this time, if the strength of the element body 2 is insufficient, the crack CR1 is introduced in the vertical direction. In addition, a crack CR2 is formed near the corner of the element body 2, extending from the end of the surrounding portion of the external electrodes 4 and 5 on the mounting surface MF side to the coil 10. In addition, as Figure 6 The illustrated mounting procedure is also applicable to the laminated coil component 1 of the present embodiment.
[0050] In contrast, in the cross section viewed from the Y-axis direction, the ratio of the first gap G1 in the Z-axis direction between the coil 10 and the mounting surface MF to the size of the element body 2 in the Z-axis direction is 12 to 30%. In this case, a distance sufficient to suppress cracks can be ensured between the mounting surface MF, which is easily deformed by stress in the element body 2, and the coil 10. Thus, cracks caused by stress during mounting can be suppressed.
[0051] In the cross section viewed from the Y-axis direction, the first gap G1 may be larger than the second gap G2 in the X-axis direction between the coil 10 and the side surfaces 2e, 2f. In this case, a distance sufficient to suppress cracks can be ensured between the mounting surface MF in the element body 2, which is easily deformed by stress, and the coil 10.
[0052] The first gap G1 may be 1.2 to 6.0 times the second gap G2. In this case, a distance sufficient to suppress cracking can be ensured between the mounting surface MF, which is easily deformed by stress in the element body 2, and the coil 10.
[0053] Here, the effect of suppressing cracks by enlarging the first gap G1 will be described in more detail. Figure 3 As shown, a region DE1 (in the region DE2 of the insulating material portion on the outer circumference side of the coil 10) having a mounting surface MF is formed. Figure 3 The region DE1 (indicated by gray in the figure) is easily deformed by the stress generated by the expansion and contraction of the conductor layers 102 and 103. Since the distance of the region DE1 in the Z-axis direction is large, the stress acting on a unit volume in the region DE1 is reduced. As a result, cracks CR1 and CR2 (see Figure 6 (c)). In addition, even if a crack CR2 is generated relative to the corner, since the coil pattern 12 of the coil 10 is greatly separated from the mounting surface MF, it is possible to prevent the crack CR2 from reaching the coil pattern 12 and breaking the wire. In addition, it is possible to prevent the crack CR2 from cutting off the magnetic flux B generated in the coil 10.
[0054] exist Figure 8 The results of an experiment to confirm the effect of enlarging the first gap G1 are shown in FIG. In this experiment, the size L1 = 275 μm, the size L2 = 185 μm, the size L3 = 360 μm, and the gap G2 = 15 μm. In contrast, six types of stacked coil components with different first gaps G1 were prepared. 100 of each type were prepared and mounted on a mounting substrate, and a crack CR1 extending in the vertical direction was observed in appearance (refer to FIG. Figure 6 The case of (c)) is considered as "crack generation" and its ratio is calculated. Figure 8 The calculation results are shown in the graph. Figure 8The vertical axis is the ratio of the number of cracks generated in 100, that is, the crack generation rate. The horizontal axis is the ratio of the gap G1 to the size L1. Figure 8 As shown in the figure, by setting the ratio of the gap G1 to the dimension L1 to 12% or more, the crack generation suppression effect can be confirmed. The plot of the ratio of "G1 / L1=9%", that is, the plot on the far left in the graph, is the existing structure of the comparative example. When the ratio is set to 12% or more, it can be confirmed that the crack generation rate (crack generation risk) can be suppressed to about half compared with the comparative example.
[0055] It can be that the first area E1 between the mounting surface MF and the coil 10 in the element body 2 forms a surface area EA constituting the mounting surface MF and an internal area EB closer to the inner side than the surface area EA, and the surface area EA has a larger average crystal grain size than the internal area EB. In this case, the generation of cracks on the mounting surface MF can be suppressed in the surface area EA having a large average crystal grain size. On the other hand, even if cracks are generated on the mounting surface MF, the internal area EB having a small average crystal grain size and pores can also suppress the progress of the cracks to the inside.
[0056] The surface area EA may be 2 to 25% of the first area E1. In this case, the effect of suppressing the generation of cracks on the mounting surface MF in the surface area EA and the effect of suppressing the propagation of cracks in the inner area EB can be balanced. Figure 7 7 (a) and 7 (b) show enlarged photographs of the vicinity of the surface area EA. Figure 7 As shown in (b), in the surface layer region EA, which is the starting point of the crack CR, the strength is high because there are few pores BA, and the crack CR is not easy to occur. Even if the crack CR occurs, in the internal region EB, because there are many pores BA, the crack CR does not advance straightly toward the inside, but extends in a random direction along the pores BA. Therefore, the progress of the crack CR is suppressed in the internal region EB.
[0057] The present invention is not limited to the above-described embodiments.
[0058] For example, you can also use Fig. 9 The structure shown. Fig. 9 As shown, the element body 2 may have a buffer portion 50 with high buffering properties on both sides in the Y-axis direction. The buffer portions 50 are respectively provided at the portions of the element body 2 having the end faces 2a and 2b. The buffer portion 50 has a structure that reduces the Young's modulus. The standard portion sandwiched by the pair of buffer portions 50 is a portion of the element body 2 whose Young's modulus is set to the value of the standard element body 2, and has a higher Young's modulus than the buffer portion 50. The size of the buffer portion 50 is not particularly limited, such as Fig. 9 As shown in (a), the buffer portion 50 can also reach the coil 10, as shown in Fig. 9As shown in (b) , the buffer portion 50 may be formed in a range that does not reach the coil 10 .
Claims
1. A laminated coil component, wherein: have: A body having a pair of first side surfaces opposite to each other in a first direction, and a pair of second side surfaces opposite to each other in a second direction orthogonal to the first direction; and a coil disposed inside the element body, wherein the coil axis extends along a third direction orthogonal to the first direction and the second direction, One of the pair of first side surfaces is a mounting surface, In a cross section viewed from the third direction, a ratio of a first gap between the coil and the mounting surface in the first direction to a size of the element body in the first direction is 12 to 30%.
2. The laminated coil component according to claim 1, wherein: In a cross section viewed from the third direction, the first gap is larger than a second gap in the second direction between the coil and the second side surface.
3. The laminated coil component according to claim 2, wherein: The first gap is 1.2 to 6.0 times the second gap.
4. The laminated coil component according to any one of claims 1 to 3, wherein A first region between the mounting surface and the coil in the element body comprises a surface region constituting the mounting surface and an inner region on the inner side of the surface region. The surface layer region has a larger average crystal grain size than the internal region.
5. The laminated coil component according to claim 4, wherein: The surface layer region is 2 to 25% of the first region.
6. A laminated coil component, wherein: have: A body having a pair of first side surfaces opposite to each other in a first direction, and a pair of second side surfaces opposite to each other in a second direction orthogonal to the first direction; and a coil disposed inside the element body, wherein the coil axis extends along a third direction orthogonal to the first direction and the second direction, One of the pair of first side surfaces is a mounting surface, In a cross section viewed from the third direction, a first gap between the coil and the mounting surface in the first direction is larger than a second gap between the coil and the second side surface in the second direction.
7. The laminated coil component according to claim 6, wherein: The first gap is 1.2 to 6.0 times the second gap.
Citation Information
Patent Citations
Electronic component
JP2012060049A